Carbachol Induces Ca2+-Dependent Contraction via Muscarinic M2 and M3 Receptors in Rat Intestinal Subepithelial Myofibroblasts - Koichi Iwanaga; Takahisa Murata; Muneyoshi Okada; Masatoshi Hori; Hiroshi Ozaki (Elsevier, 2009)
Abstract.: Intestinal myofibroblasts (IMFs) that exist adjacent to the basement membrane of intestines have contractility and contribute to physical barriers of the intestine. Nerve endings distribute adjacent to IMFs, suggesting neurotransmitters may influence IMFs motility; however, there is no direct evidence showing the interaction. Here, we isolated IMFs from rat colon and investigated the effect of acetylcholine on IMFs contractility. In the collagen gel contraction assay, carbachol (1 - 10 μM) and the muscarinic receptor agonist bethanechol (30 - 300 μM) dose-dependently induced IMFs contraction. Pretreatment with the muscarinic receptor antagonist atropine (1 - 10 nM) inhibited carbachol-induced contraction. In RT-PCR, mRNA expression of all muscarinic receptor subtypes (M1 -M5) was detected in IMFs. Subsequently we found pretreatment with the muscarinic M2 receptor antagonist 11-([2-[(diethylamino)methyl]-1-piperdinyl]acetyl)-5,11-dihydro-6H-pyrido[2,3-b][1,4]benzodiazepine-6-one (AF-DX116) (10 and 30 nM) or the muscarinic M3 receptor antagonist 4-diphenylacetoxy-N-methyl-piperidine (4-DAMP) (3 and 10 nM) dose-dependently inhibited carbachol-induced contraction. In Ca2+ measurement, 1 - 10 μM carbachol and 30 - 300 μM bethanechol elevated the intracellular Ca2+ concentration ([Ca2+]i) in IMFs. Atropine (10 nM) eliminated carbachol-induced [Ca2+]i elevation. The Ca2+-channel blocker LaCl3 (3 μM) abolished carbachol-induced [Ca2+]i elevation and contraction. Furthermore, AF-DX116 and 4-DAMP dose-dependently inhibited the carbachol-induced [Ca2+]i elevation. These observations suggest that acetylcholine elicits Ca2+-dependent IMF contraction through muscarinic M2 and M3 receptors. Keywords:: intestinal myofibroblast, acetylcholine, contraction, muscarinic M2 receptor, muscarinic M3 receptor